An Investigation of Shared Value, Benefit, Commitment, Trust and Retention in the Banking Sector: A Student Perspective - E., Chinomona; ., Sandada. M (Journal of Economics and Behavioral Studies, 2014)
Despite the increase in research focusing on service relationship level in the banking sector, research on relationship benefit, student perceived shared value on relationship commitment, trust and student retention in the African banking context is still scant. Therefore, using a data set of 175 from students in colleges and universities in Johannesburg, this study examines these relationships. Smart PLS software technique was used to statistically analyse the measurement and structural models. All the posited six hypotheses were supported. The findings from the data analysis proved that there is a strong positive relationship between all six hypotheses.